القيم الجمالية للفن الجديد " الآرت نوفو " و الاستفادة منها في عمل مشغولات معدنية معاصرة - أحمد، عبدالرحمن محمد ربيع; بيومي، شيماء مجدي عبدالله (جامعة عين شمس - كلية التربية النوعية, 2014)
Find a problem: Determined by the research problem in the next question: How to take advantage of the trappings Nouveau building in the busy contemporary metal to enrich the aesthetic values of the mineral busy? Imposition of Search: There is a positive relationship between capitalizing on aesthetic values of the trappings Nouveau and contemporary metal building busy. Aim of the research: Access to new art formulations for new art decorations formations (Nouveau) to enrich the field of education in the field of metal working, Department of Art Education. The importance of Search: The development of students' ability in the visual detection of aesthetic values of the trappings (Nouveau) and how to employ them to build a busy contemporary metal. Search Terms: Art Nouvea: " Is a term Belgian _ French art movement emerged in the period between (1920:1880) reaction Thaer on the art of traditional classical, came to bear their philosophy meaning of freedom in the form of icons dating back to the Arts old with values Fine opened the artist EU path for creativity and Alaseltham, came label proportion to the Design Gallery which was opened by Samuel Bing Hall Show, dubbed the new art. "(p. 811_7) Find the limits: Limited research on the following measures: The study is limited to a subjective experience of the researcher. Research Methodology: Track study descriptive method and analytical approach Altejreby through two frameworks: First: a descriptive study analytical Nouveau decorations in terms of: Intellectual properties and new Fine Art. .Almaatherat that influenced the new art Some of the pioneers of the new art. Some metal work for artists new art. Second: Investment aesthetic values of art nouveau in the work of contemporary metal artifacts.
Keywords: الفنون التشكيلية -- الفن التجريدي -- الفنانون التشكيليون -- اللوحات الفنية